Strategi Kebijakan Pembangunan Berkelanjutan Wisata Pantai Di Kawasan Lombok Timur - Suhastini, Novia (KOMUNITAS, 2019)
The development of tourism which has recently been highlighted by the mass media in Indonesia with the government's program in tourism development as an addition to foreign exchange from the non-oil and gas sector. The tourism development program, which has been launched since 1988, is expected to attract the presence of foreign tourists and domestic tourists, which in turn will benefit the country's financial income. The exoticism of the beach has become one of the tourist strengths of East Lombok Regency. Along the coast in the south eastern Lombok region, lined with very attractive beaches. The development of attractions that are constrained by infrastructure, especially the problem is the lack of electricity and roads for access to locations are inadequate. The problem solving, it takes a policy of analyzing tourism policies in East Lombok Regency must pay attention; policy alternaitf, Policy implementation and policy evaluation.